Development and validation of a novel stability indicating HPLC method for the separation and determination of darolutamide and its impurities in pharmaceutical formulations - Kamani, V.G.; Sujatha, M.; Daddala, G.B. (KU Publ., 2021)
This study reports for the first time about a stability indicating RP-HPLC method for analysis of darolutamide and its impurities 1, 2, and 3 in bulk and formulations. The separation was achieved on Phenomenex column with Luna C18 (250 mm × 4.6 mm, 5 μm) as stationary phase, and 50 mM ammonium acetate: methanol solution 15:80 (v/v) at pH 5.2 as mobile phase at 1.0 mL/min flow rate. UV detection was carried at wavelength of 239 nm. In these conditions the retention time of darolutamide and its impurities 1, 2, and 3 was 7.05, 8.90, 4.63 and 5.95 min, respectively. The method was validated for system suitability, range of analysis, precision, specificity, stability, and robustness. Forced degradation study was done through exposure of the analyte to five different stress conditions and the % degradation was small in all degradation condition. The proposed method can separate and estimate the drug and its impurities in pharmaceutical formulations. Hence, the developed method was suitable for the quantification of darolutamide and can separate and analyse impurities 1, 2, and 3.
Даролутамид пен оның фармацевтикалық препараттардағы қоспаларын бөлу және анықтау үшін жаңа сенімді ЖТСХ әдісін жасау және валидациялау
Разработка и валидация нового надежного метода ВЭЖХ для разделения и определения даролутамида и его примесей в фармацевтических препаратах
Keywords: darolutamide; impurity analysis; HPLC method development; method validation; ruggedness; forced degradation study; formulation assay; impurity analysis in Nubeqa